1997
DOI: 10.1016/s0006-3495(97)78252-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-gramicidin interactions using two-dimensional Fourier-transform electron spin resonance

Abstract: The application of two-dimensional Fourier-transform electron-spin-resonance (2D-FT-ESR) to the study of lipid/gramicidin A (GA) interactions is reported. It is shown that 2D-FT-ESR spectra provide substantially enhanced spectral resolution to changes in the dynamics and ordering of the bulk lipids (as compared with cw-ESR spectra), that result from addition of GA to membrane vesicles of dipalmitoylphosphatidylcholine (DPPC) in excess water containing 16-PC as the lipid spin label. The agreement between the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(100 citation statements)
references
References 44 publications
(102 reference statements)
5
94
1
Order By: Relevance
“…In the presence of IB the S c+ and S cÀ signals are quite different, with the S cÀ spectra being substantially sharper due to the echolike cancellation of the IB, which does not occur for the S c+ spectra. In our past studies [7,9] we have found that the S c+ signal is much more attenuated, due to its more rapid decay during t d , because the IB is not refocused. Thus, we make use of the strong and better resolved S cÀ signal.…”
Section: D-eldormentioning
confidence: 91%
See 3 more Smart Citations
“…In the presence of IB the S c+ and S cÀ signals are quite different, with the S cÀ spectra being substantially sharper due to the echolike cancellation of the IB, which does not occur for the S c+ spectra. In our past studies [7,9] we have found that the S c+ signal is much more attenuated, due to its more rapid decay during t d , because the IB is not refocused. Thus, we make use of the strong and better resolved S cÀ signal.…”
Section: D-eldormentioning
confidence: 91%
“…It is important to note that in all three steps (i, ii, and iii) a set of 2D-ELDOR spectra for several mixing times, T m are simultaneously fit [3,[6][7][8][9][10][11]. In the full S cÀ method, this set of spectra vs. T m are fit to the same phase corrections, since all the experimental settings are kept constant, except for T m .…”
Section: The Full S Cà Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These matters ate discussed below. In recent years it has been shown that 2-D ELDOR experiments on spin-labeled lipids in membranes provide much greater spectral resolution to dynamics and ordering in these complex fluids than continuous-wave (CW) ESR spectra are capable of [7,8]. In a study of several different types of spin-labeled lipids in membrane vesicles, it was shown recently that when they are in the ordinary liquid crystalline or liquid-disordered (Ld) phase their 2-D ELDOR spectra are markedly different from those in the liquid-ordered (Lo) phase, which is obtained by adding substantial amounts of cholesterol to the phospholipid.…”
mentioning
confidence: 99%